'I lost my job suddenly, but I was prepared': the significance of urban and peri-urban agriculture in Benin City, Nigeria. Issue 1 (2nd January 2023) - Uko, Emaediong; Binns, Tony; Nel, Etienne
ABSTRACT: In the rapidly growing cities of the Global South, and Africa in particular, urban and peri-urban agriculture (UPA) is increasingly recognized as a survival strategy both by researchers and international development organizations. While UPA is well researched, direct links to economic crisis and class variations in participation have only received limited attention in the Nigerian context. This study focuses on Benin City, the second largest city in Nigeria's southern oil producing region, where repeated and unpredictable fluctuations in oil prices have significant implications for livelihoods. The paper discusses the results of field-based data collected using qualitative research methods (observation, in-depth interviews and questionnaire surveys) in Benin City, Southern Nigeria, where there is a dearth of published material on the practice of UPA . The paper reveals that in the context of unpredictable and frequent exposures to economic shocks, households at all socio-economic levels depend significantly on food production activities, not only for their immediate survival, but as a means of reducing household vulnerability and building resilience against future shocks.